Genetic link between KIF1A mutations and amyotrophic lateral sclerosis: evidence from whole-exome sequencing - Zheng, Wei; He, Ji; Chen, Lu; Yu, Weiyi; Zhang, Nan; Liu, Xiaoxuan; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2024)
Objectives Genetics have been shown to have a substantial impact on amyotrophic lateral sclerosis (ALS). The ALS process involves defects in axonal transport and cytoskeletal dynamics. It has been identified that KIF1A, responsible for encoding a kinesin-3 motor protein that carries synaptic vesicles, is considered a genetic predisposing factor for ALS.The analysis of whole-exome sequencing data from 1068 patients was conducted to examine the genetic link between ALS and KIF1A. For patients with KIF1A gene mutations and a family history, we extended the analysis to their families and reanalyzed them using Sanger sequencing for cosegregation analysis.In our cohort, the KIF1A mutation frequency was 1.31% (14/1068). Thirteen nonsynonymous variants were detected in 14 ALS patients. Consistent with the connection between KIF1A and ALS, the missense mutation p.A1083T (c.3247G>A) was shown to cosegregate with disease. The mutations related to ALS in our study were primarily located in the cargo-binding region at the C-terminal, as opposed to the mutations of motor domain at the N-terminal of KIF1A which were linked to hereditary peripheral neuropathy and spastic paraplegia. We observed high clinical heterogeneity in ALS patients with missense mutations in the KIF1A gene. KIF5A is a more frequent determinant of ALS in the European population, while KIF1A accounts for a similar proportion of ALS in both the European and Chinese populations.Conclusions Our investigation revealed that mutations in the C-terminus of KIF1A could increase the risk of ALS, support the pathogenic role of KIF1A in ALS and expand the phenotypic and genetic spectrum of KIF1A-related ALS.